N-Acetylcysteine Ameliorates Gentamicin-Induced Nephrotoxicity by Enhancing Autophagy and Reducing Oxidative Damage in Miniature Pigs. Issue 6 (December 2019) - Cui, Jing; Tang, Li; Hong, Quan; Lin, Shupeng; Sun, Xuefeng; Cai, Guangyan; Bai, Xue-Yuan; Chen, Xiangmei
Abstract : ABSTRACT: The clinical use of gentamicin over prolonged periods is limited because of dose and time-dependent nephrotoxicity, in which intracellular oxidative stress and heightened inflammation have been implicated. Macroautophagy/autophagy is an essential and highly conserved self-digestion pathway that plays important roles in the maintenance of cellular function and viability under stress. The aim of this study was to determine changes in autophagy in response to the antioxidant N-acetylcysteine (NAC), via its effects on oxidative stress, inflammation, apoptosis, and renal function, following treatment with gentamicin in mini pigs. Adult mini pigs were divided into isotonic saline solution, gentamicin, and gentamicin plus NAC combination treatment groups. Gentamicin-induced histopathological changes, including inflammatory cell infiltration and tubular necrosis, were attenuated by NAC. NAC ameliorated the gentamicin-induced decreases in the levels of autophagy-related proteins, such as LC3 (microtubule-associated protein 1 light chain 3), PINK1 (phosphatase and tensin homologue deleted on chromosome10-induced kinase 1), phospho-parkin, AMBRA1 (activatingmolecule in Beclin 1-regulated autophagy), p62/SQSTM1 (sequestosome protein 1), and polyubiquitinated protein aggregates. NAC also caused a significant reduction in oxidative damage markers, including 4-hydroxy-2-nonenal, protein carbonyls, γ-H2AX (gamma histone variant H2AX), and 8-hydroxy-2′-deoxyguanosine, in gentamicin-treated animals. These data show that the protective effects of NAC might be related, at least in part, to a reduced inflammatory response, as observed in animals treated with both gentamicin and NAC. These results suggest that autophagy could be a new therapeutic target for preventing gentamicin-induced kidney injury, and that NAC might ameliorate gentamicin-induced nephrotoxicity by autophagy.